Genetic diversity of Mycobacterium tuberculosis complex strains isolated from livestock workers and cattle in Nigeria (2019)
molecular typing techniques are useful in understanding tuberculosis epidemiology;yet,they have been under-utilized at the human-animal interface in nigeria. Sixty-four mycobacterium tuberculosis complex(MTBC) isolates including 42 M. tuberculosis,13 M. bovis and nine M. africanum obtained from livestock workers(LW,n=47) and their cattle (n=17) in three geographical zones of Nigeria were genotyped to identify and evaluate the genetic diversity of the circulating MTBC using spoligotyping. distribution into clades of M. tuberculosis revealed;45.3% Uganda I-[SIT46-cattle: 1;LW:28], 14.1% latin american mediterranean-[SIT61,cattle:LW:8], and 1.6% T-[SIT53_LW:1]. The M. bovis strains were 6.3% SB0944[CATTLE:4] and 1.6% each of SB0300,SB1026,SB1027 and SB1439[CATTLE:4]. Seventeen MTBC isolates [cattle:7;LW:10] yielded 14 new spoligotype patterns including three M. tuberculosis strains (three isolates), five M. bovis strains (five isolates) and sixM. AFRICANUM STRAINS (NINE ISOLATES), two of which belonged to MAF1. only few families namely, the not previously described Uganda i-,LAM and SB0944 are predominant among the LW and cattle, with other types in lower prevalences. the strain population structure indicates an intriguing diversity and possible zoonotic linkage with consequences for TB control in the country. the need to employ newer molecular techniques such as mycobacterial interspersed repetitive unit-variable number tandem repeats and whole genome sequences to decipher circulating MTBC strains in Nigeria is advocated.